PERANCANGAN SISTEM INFORMASI PADA LAUNDRY SEPATU KLINSNIKRS BERBASIS WEBSITE DENGAN PENAMBAHAN FITUR TRACKING - Rafi Satrio Wikamto (2023)
Klinsnikrs is a laundry business that focuses on washing shoes and bags. the problem that exists in the current laundry service system at klinsnikrs is the service administration process that has not used a computerized system. Starting from customer data which is still recorded on paper and recorded in the laundry receipt. And also the revenue results have not been calculated and stored using a computerized system, this really takes a long time to calculate and errors often occur. For this reason, the system monitors the workmanship stage of the shoe and bag laundry using a website, which is able to determine the workmanship stage accurately. Klinsnikrs presents this technology into an information system in real time based on the website. With the Klinsnikrs application, it can help employees in carrying out their duties and make it easier for customers to find out information that has been updated by employees and other workers. This shoe laundry business requires an information system using an application called Klinsnikrs to simplify the work and tasks of the employees involved. So an application was made by analyzing the system with the PIECES method. Then design and build a website-based Klinsnikrs application using the Waterfall method. This research produces an information system that is useful to support the performance of the shoe laundry business.